Comparison of Cytokine RANTES/CCL5 Inflammation in Apical Periodontitis and in Jawbone Cavitations – Retrospective Clinical Study - Vasconcelos e Cruz J; Notter F; Schick F; Lechner J (Dove Medical Press, 2024)
Joana Vasconcelos e Cruz,1,2 Florian Notter,3 Fabian Schick,3 Johann Lechner4 1Dental Materials, Egas Moniz School of Health & Science, Caparica, Portugal; 2Dental Materials, Centro de Investigação Interdisciplinar Egas Moniz (CiiEM), Caparica, Portugal; 3Dental Surgeon, Clinic for Integrative Dentistry, Munich, Germany; 4Head, Clinic for Integrative Dentistry, Munich, GermanyCorrespondence: Johann Lechner, Gruenwalder Str. 10A, Munich, 81547, Germany, Tel +49 89 697 0129, Fax +49 89 692 5830, Email drlechner@aol.comBackground: Apical periodontitis (AP) is one of the most common endodontic diseases associated with osteo destructive cytokine production. The literature also reports cytokine studies in fatty degenerative osteonecrotic bone marrow defects (BMDJ/FDOJ) independent of AP.Objective: We compare the RANTES/CCL5 (R/C) chemokine production between AP and BMDJ/FDOJ. For both pathologies, the R/C expression was also compared to radiographic diagnosis in 2D-OPG, 3D-CBCT/DVT.Material and Methods: Postoperative samples were collected and divided in three different groups: HB (healthy jawbone) (n=19), APs (n=19), and BMDJ/FDOJ (n=7). The R/C expression was evaluated using multiplex analysis. In addition, two clinical cases from AP and BMDJ/FDOJ groups were randomly selected and radiographic diagnosis in 2D-OPG and 3D-CBCT/DVT was compared to TAU measurements and R/C expression in AP and in BMDJ/FDOJ.Results: BMDJ/FDOJ showed the highest R/C expression (2498.71 pg/mL), followed by AP (841.85 pg/mL) and HB (149.85 pg/mL) (AP vs BMDJ/FDOJ = p=0.01; AP vs HB = p=< 0.01; BMDJ/FDOJ vs HB = p=< 0.01). In both clinical cases, the radiographic findings depict the AP areas in OPG and CBCT/DVT, in contrast to the BMDJ/FDOJ areas. Conversely, the systemic immunological R/C expressions are threefold and fivefold excessive in both cases.Discussion: AP is recognized as a pathology requiring treatment, while the pathogenesis of BMDJ/FDOJ is controversially discussed in the literature, despite stronger potential systemic immunological effects (breast cancer (case 1) and multiple sclerosis (case 2)). The inadequate radiographic representation of reduced bone density in BMDJ/FDOJ areas could be a reason for this contradiction.Conclusion: The data presented provide the first quantitative analysis of R/C expression in AP and BMDJ/FDOJ. BMDJ/FDOJ showed high R/C expression than AP, besides the diagnostic through radiographs being extremely poor. To cover this imprecision, a radiation-free TAU device is available. Keywords: bone marrow, RANTES/CCL5, apical periodontitis, osteonecrosis, dental radiography, ultrasonography